Knowing Britten - Bedford, Steuart 1939-2021; Gillett, Christopher 1958- (Bittern Press, 2021)
Knowing Britten is a vivid and insightful account of Steuart Bedford's long association with both Britten the man and his music The conductor and pianist Steuart Bedford (199-2021) could not remember a time when he did not know Benjamin Britten. His mother, Lesley Duff, sang with the English Opera Group in the premieres of The Rape of Lucretia and Albert Herrring in the late 1940s, and the family was closely involved with Britten and Pears for many years. Following his music studies and time on the music staff at Glyndebourne, Bedford joined the English Opera Group, gradually becoming Britten's trusted surrogate conductor. As Britten's health began to fail, Before took on responsibility for the premiere of Death in Venice, including its US premiere at the Metropolitan Opera, New York, and the dramatic cantata Phaedra among others